The Penal Policy Formulation in Cyberporn Crime Countermeasures - Wirya Darma, I Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 1 (2021)DO - 10.24843/JMHU.2021.v10.i01.p03, 2021)
Criminal law reform must refer to the penal policy. The penal policy can be interpreted as holding a selection to achieve the best results of criminal legislation that meets the requirements of justice and effectiveness. Penal policy in the eradication of cyberporn is always associated with the advancement of technology that can not be separated from the development of the society that utilizes internet technology in various fields both in the fields of education, offices, and companies and so on. Through crime countermeasures policies using penal means, the existence of a law is obviously expected to further enhance the repressive function of criminal law. One of the efforts to tackle cyberporn crimes through the penal means is to apply the provisions of applicable laws such as the Criminal Code, Law Number 40 of 1999 concerning the Press, Law Number 32 of 2002 concerning Broadcasting, Law Number 19 of 2016 concerning Information and Electronic Transactions, Law Number 33 of 2009 concerning Film. However, apparently, the law still has limitations to compensate for the increasingly rapid development of cyberporn, including the provision of unclear pornographic restrictions. Therefore it is necessary to have a revision in Indonesian criminal law, especially against the Criminal Code which is a product of the legacy of the Dutch colonial era.